Complete Genome Sequences of 10 Lactococcal Skunavirus Phages Isolated from Cheddar Cheese Whey Samples in Canada - Doré, Laurie (Microbiol Resour Announc, 2021)
We report the complete genome sequences of 10 virulent phages of the Skunavirus genus (Siphoviridae) that infect Lactococcus lactis strains used for cheddar cheese production in Canada. Their linear genomes range from 28,969 bp to 31,042 bp with GC contents of 34.1 to 35.1% and 55 to 60 predicted open reading frames (ORFs).